POETICAL DESCRIPTION OF TIME AND SPACE IN SHORTS (International conference on multidisciplinary science, 2025)
The chronotope problem is the most researched concept today. This article explores the literary space and time in Tahir Malik's fantastic stories. The space and time described in the stories “Davron”, “Falak”, “Hunting” and the skills of the writer are analyzed in detail. Tahir Malik's style of creating a fantastic story is also discussed.